1980
DOI: 10.1227/00006123-198008000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal Bone Cyst of the Temporal Bone Presenting as a Spontaneous Intracerebral Hemorrhage

Abstract: An aneurysmal bone cyst originating from the squamous portion of the left temporal bone is reported. The lesion presented in a 62-year-old nonhypertensive man as a spontaneous, intraparenchymal left temporal lobe hematoma. No evidence of trauma, hermorrhagic diathesis, or concurrent systemic disease was found. Previous case reports of aneurysmal bone cysts of the skull are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…Treatment modalities range from simple surgery to a combination of methods. Although curettage followed by bone grafting is the most commonly employed modality, it has a high recurrence rate of 20%-40% (7,11,15,16). In the present case, the cyst was completely and aggressively scraped out to decrease the chance of recurrence.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Treatment modalities range from simple surgery to a combination of methods. Although curettage followed by bone grafting is the most commonly employed modality, it has a high recurrence rate of 20%-40% (7,11,15,16). In the present case, the cyst was completely and aggressively scraped out to decrease the chance of recurrence.…”
Section: Discussionmentioning
confidence: 70%
“…In the present case, the cyst was completely and aggressively scraped out to decrease the chance of recurrence. The remaining cavity was filled with donor bone tissue (allograft), bone chips (autograft), or other materials (2,3,6,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Focal neurologic deficits, proptosis, signs of increased ICP, headache and conductive hearing loss may be found depending on location of the tumor [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. The temporal petrous bone is an extremely rare location for this neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature found 15 cases of ABC of the temporal bone, and only 1 report which involves the petrous bone [5, 6, 7, 8, 9, 10, 11, 13, 14, 15, 16, 21]. Information for analysis was available for 12 of these cases (table 1) [5, 6, 7, 8, 9, 10, 11, 13, 14, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation